Case studies: perplexing thyroid function test results - Shahar, Mohammad Arif (Malaysian Endocrine & Metabolic Society (MEMS), 2016)
Thyroid function test plays an important role in diagnosis and management of various thyroid disorders. Although the interpretation of thyroid function test is often straightforward, it is not uncommon to have situations where the process can be challenging.